Formulation, characterization, and in vitro simulated gastrointestinal fluid analysis of chewable yogurt tablet incorporated with corncob fiber - Chan, Yong Lin; Jamalullail, Nurul Aini; Tan, Chin Ping; Abdul Manap, Mohd Yazid; Tang, Teck Kim; Lee, Yee Ying; Phuah, Eng Tong; Lai, Oi Ming (Universiti Putra Malaysia Press, 2024)
This study formulates and evaluates a novel functional food, corncob fiber-infused chewable yogurt tablets, to enhance nutritional value. The tablets have the potential to alleviate gastrointestinal symptoms in the elderly and combat malnutrition in selective eaters, potentially replacing multiple supplement tablets. Four batches of tablets underwent rigorous evaluation, considering physicochemical properties, shelf life, and probiotic viability in simulated gastrointestinal conditions. All tablets exhibited robust stability against simulated fluids (85–90% survival rate) and met desired physicochemical benchmarks. Notably, F1 had the lowest hardness (9.50 kp/cm2), while tensile strength showed no significant variance (0.93–1.18 N/mm2) between tablets. However, F3 and F4 displayed significantly longer disintegration times (41.11–52.82 min). After three months, the average bacterial viability was 7 log no. CFU/g, highlighting the tablets’ potential to deliver intact probiotics for immediate beneficial effects upon consumption. Thus, these chewable yogurt tablets offer a promising means to deliver probiotics effectively while addressing specific dietary challenges.